THE CORRELATION BETWEEN TOOTH LOSS AND NUTRITIONAL STATUS IN ELDERLY IN SOUTH DAHA DISTRICT - Benedictus Dimas Aryo Prakoso; Rahmad Arifin; Fajar Kusuma Dwi Kurniawan (Universitas Lambung Mangkurat, 2023)
Background: Aging is a biological process that will occur in every human individual. According to the Law of the Republic of Indonesia, the elderly is someone who reached age of 60 years and over. Based on data from BPS Indonesia in 2021, there are 29.3 million elderly in Indonesia and in South Daha District 3,534 elderly. Tooth loss can make the elderly vulnerable to decreased quality of life. Tooth loss cases will interfere with masticatory function and decreasing nutritional status. Objective: This study aims to analyze the correlation between tooth loss and nutritional status in the elderly in South Daha District. Methods: This study is a correlational analytic study with a cross sectional approach. The research sample are 105 elderly. Data collection includes primary data that obtained through direct examination of the number of tooth and BMI. Data analysis used univariate and bivariate with the Spearman’s test. Results: The results showed that most of the respondents had a low level of tooth loss (43.8%) and normal nutritional status (58.1%). The Spearman test showed that there was a significant correlation between tooth loss and nutritional status. Conclusion: There is a significant correlation between tooth loss and nutritional status in the elderly in South Daha DistrictKeywords: Elderly, Nutritional Status, South Daha District, Tooth Loss